Perceptions by pregnant and childbearing-age women in southern Brazil towards teratogenic risk from medicines and radiotherapy - Emilia da Silva Pons; Tatiane da Silva Dal Pizzol; Daniela Riva Knauth (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
Mistaken perception of teratogenic risk can keep pregnant women from using safe medicines. The current study analyzed women's concepts and perceptions towards teratogenic risk from medicines and exposure to radiotherapy during pregnancy. The quantitative data resulted from interviews with 287 pregnant and non-pregnant women. Two qualitative focus groups were conducted. No significant differences were observed between the two groups in terms of perceptions of teratogenic risk. Median perceptions of non-teratogenic exposures (paracetamol and metoclopramide) were close to the expected values, while higher values were found for teratogenic exposures (misoprostol and radiotherapy). The logic women used to estimate risk was classification of medicines as "strong" or "weak". Medicines perceived as "weak" by the women do not pose any teratogenic risk, as shown by the median perceptions close to the true values. Meanwhile, "strong" medicines were viewed as dangerous, thus explaining the high median perceptions of teratogenic exposures.